Analisis Keabsahan Sertifikat Hak Guna Bangunan yang Terbit diatas Laut - Syahril Hidayat; Melly Rifa’atul Lailiyah; Rizki Nurdiansyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research analyzes the validity of Building Use Rights (HGB) certificates over the sea using normative legal research methods. The research focus includes validity variables, HGB certificates, and the sea, by examining related laws and regulations, legal principles and doctrines. The research results show that the validity of HGB certificates over the sea is determined by conformity with legal provisions, the status of the sea area, and certificate issuance procedures. This research provides an in-depth understanding of the challenges and legal solutions in cases of HGB certificates over the sea. The research results show that the validity of HGB certificates over the sea depends on compliance with legal provisions, maritime area status, and issuance procedures. However, the issuance of HGB over the sea faces legal challenges due to the absence of a clear legal basis in the UUPA, while the sea is subject to the maritime and environmental legal regime.